Strategi Peningkatan Penyampaian Informasi melalui Hierarki Visual pada Media Publikasi Digital LPPM Universitas Tarumanagara - Matthew Ricky Wijaya; Ruby Chrissandy (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
This activity was motivated by the need of the Tarumanagara University Research and Community Service Institute to provide digital publication media that is informative, communicative, and easy for the academic community to understand. Academic information presented through digital posters typically includes many elements, such as the event title, date and time, speakers, registration links, QR codes, and contact information. If these elements are not arranged according to the appropriate visual hierarchy, the effectiveness of information delivery may decrease. This initiative aims to assist partners in designing digital publication media based on the principles of visual hierarchy. The implementation method involved identifying partners’ needs, analyzing information content, developing visual concepts, designing digital posters, conducting joint revisions with partners, and implementing the publication media. The results of the activity show that the application of visual hierarchy through the adjustment of font size, layout, color contrast, typographic emphasis, and reading flow helps make the publications more structured, easier to read, and more effective in presenting key information. This activity provides a direct benefit to partners in the form of digital publications that are more communicative and aligned with the academic information service needs of the Research and Community Service Institute (LPPM) at Tarumanagara University.